An investigation of the in-game behaviours of professional, top-level youth soccer coaches - Smith, M.; Cushion, C. J. (Journal of Sports Sciences, 2006)
Although research into coaching has increased considerably during the last two decades, an area of neglect has been that of the professional youth coach. The aim of this study was to investigate the working behaviours of six top-level professional soccer coaches. Data were collected using a modified version of the Arizona State University Observation Instrument and semi-structured interviews. The triangulation of the data ensured that both the "what" and the "why" of the coaches' behaviour were considered. Results revealed a conscious and well thought out pattern of behaviour: silently monitoring, interspersed with clips of instruction coupled with praise and encouragement. The interviews revealed three themes underpinning this behaviour: developing game understanding, support and encouragement, and coaches' role and influences. The use of silence was the largest single behaviour, the efficacy of which was considered in light of theories of experiential and discovery learning.